Efficacy of ultrasound-guided single-injection erector spinae plane block for thoracoscopic wedge resection: a prospective randomized control trial. Issue 12 (23rd September 2022) - Klaibert, Beau; Lohser, Jens; Tang, Raymond; Jew, Michael; McGuire, Anna; Wilson, Jason
Abstract : Background: Despite advances in minimally invasive thoracic surgery, patients remain at risk of adverse pulmonary events with suboptimal postoperative analgesia. Novel methods of regional analgesia are warranted. Our objective was to prospectively evaluate the impact of ultrasound-guided single-injection erector spinae plane (ESP) block with ropivacaine compared with placebo control on standard of care postoperative recovery in subjects undergoing video-assisted thoracoscopic surgery (VATS) wedge resection. Methods: This prospective, randomized, placebo-controlled, double-blinded study was conducted at a tertiary thoracic surgical center. Consecutive subjects undergoing VATS wedge resection were randomized to receive a single-injection ESP block with 0.5% ropivacaine or 0.9% saline placebo, in addition to the current standard of care of multimodal analgesia including patient-controlled analgesia and surgical local anesthetic wound infiltration. The primary outcome was difference in 40-point Quality of Recovery (QoR-40) on day 1 postoperatively. The secondary outcomes included opioid consumption, Visual Analog Pain Scale (VAS) score, time spent in the postanesthesia care unit (PACU), and block-related and postoperative complications. Results: Eighty subjects were enrolled, 40 in each group, with 76 completing follow-up (38 subjects in each group). There was no difference in the median QoR-40 score between groups, 169.5 for the ropivacaine group and 172.5 for the control group (difference 3, p=0.843). No significant differences existed between groups in all secondary outcomes, with the exception of the ropivacaine group having lower VAS pain scores measured at 1 hour postoperatively and a shorter duration of stay in the PACU of 117 min. Conclusions: Following VATS wedge resection, the addition of an ESP block with ropivacaine to standard multimodal analgesia is unlikely to add meaningful clinical value. Trial registration number: NCT03419117 .